FRI0466 RISK FACTORS ASSOCIATED WITH THE DEVELOPMENT OF FRACTURES IN GLUCOCORTICOID TREATED PATIENTS. THE ROLE OF HYPOGONADISM. (June 2019) - Florez, Helena; Hernández-Rodríguez, José; Muxi, Africa; Carrasco, Josep Lluís; Prieto-González, Sergio; Ruiz-Gaspà, Silvia; Cid, Maria C.; Monegal, Ana; Guañabens, Núria; Peris, Pilar
Abstract : Background: Glucocorticoid-induced osteoporosis (GIOP) is a common form of secondary osteoporosis (OP). Fractures in GIOP frequently occur with higher bone mineral density (BMD) than expected and typically at treatment initiation, complicating the identification of patients at risk for fracture. Objectives: Identify risk factors associated with fragility fracture development in GC-treated patients. Methods: 127 patients (aged 62±18years, 63% women, 46% postmenopausal) on GC treatment (prednisone ≥5mg/day, >3months) were included. Clinical data collected included: risk factors for OP and fractures, dose and GC-treatment duration, previous fractures and disease activity, anthropometric data, bone metabolism parameters (including gonadal axis study), BMD analysis (DXA; OP: T-score ≤-2.5), TBS (degraded microarchitecture [DMA]:<1.230), dorsolumbar X-ray (assessing vertebral fractures [VF]) and FRAX risk (GC-adjusted) 1 . Results: Most patients received GC treatment for vasculitis or polymyalgia rheumatica during 47.7±69 months (mean daily dose: 14.5mg). 17% had VF, 28% had fragility fracture (VF + non-VF), 29% OP and 71% DMA. Patients with VF received more GC-boluses (57.1% vs. 29.5%, p=0.03), were older (68±13 vs. 60±19 years, p=0.02), postmenopausal (100% vs. 67%, p=0.015) and/or men with testosterone <250ng/dL (57% vs. 11%, p=0.017) and had lower TBS values (1.100 vs. 1.220, p<0.001) and higher FRAX risk (17 vs. 9, p=0.003); patients with fragility fractures showed higher accumulated GC-doses (6.1±13 vs. 8±18g, p=0.046). On multivariate analysis, hypogonadism (OR 14.3; IC95% 2.2->100, p=0.01) and having received GC-boluses (OR 3.40; IC95% 1-11.8, p=0.01) were the principal factors associated with VF. Hypogonadism (OR 7.1; IC95% 1.5-38.7, p=0.01) and having a FRAX >20 (OR 6.97; IC95% 1.3-51.7, p=0.02) were factors related to the presence of fragility fractures. Men with testosterone <250ng/dL had higher BMI (29.4 vs. 26.3, p=0.005) and disease activity (ESR 23 vs. 12, p=0.005) and lower TBS (1.050 vs. 1.210, p<0.001); age, daily and cumulated GC doses were similar to subjects with normal testosterone levels. Conclusion: Hypogonadism is a major risk factor for developing fractures in GC-treated men and women, whereas receiving GC-boluses is related to VF, indicating the importance of evaluating the gonadal axis in these patients. References: [1] Buckley L, et al. Arthritis Care Res. 2017 Disclosure of Interests: Helena Florez: None declared, José Hernández-Rodríguez : None declared, Africa Muxi: None declared, Josep Lluís Carrasco: None declared, Sergio Prieto-González: None declared, Silvia Ruiz-Gaspà : None declared, Maria C. Cid Grant/research support from: Kiniksa Pharmaceuticals, Consultant for: Roche, GSK, Janssen, Abbvie, Speakers bureau: Boehringer-Inhelheim, Vifor, Ana Monegal Speakers bureau: Eli Lilly, Amgen, Núria Guañabens Consultant for: Advisory Boards from Amgen, Alexion and UCB, Speakers bureau: Fees and lectures from Eli Lilly, Pilar Peris Speakers bureau: Personal Fees and Non-financial support (attendance to congresses) from Amgen and Eli Lilly